Importance of Pharmacist in Oxaliplatin Hepatotoxicity Associated with Inadequate Nutritional Diet: Case Report - Cavalcanti, Iago D.L.; Costa, Diogo T.; de Aguiar Silva, Andreza T.; Peres, Adrya L.; de Oliveira Coimbra, Cynthia G. (Current Nutrition & Food Science, 2020)
A 40 years old male with colorectal cancer, with an unbalanced hypercaloric diet, attempted, on his own initiative, to gain weight, without nutritional follow-up, during chemotherapy treatment with oxaliplatin protocols, without pharmaceutical guidance. When initiating the new protocol, with oxaliplatin/irinotecan combination therapy, he presented symptomatology suggestive of hepatic injury during the administration of oxaliplatin. When performing a Magnetic Resonance Imaging of the total abdomen, hepatic nodules were identified indicating lesions resulting from the chemotherapy treatment, and blood tests indicated Aspartate aminotransferase levels in 55 U/L and Alanine aminotransferase in 68 U/L. The patient underwent partial hepatectomy for the removal of the nodules and was currently in clinical care, presenting a frame stable but non-therapeutic possibility. This case highlights the importance of interaction among health professionals, reinforcing the need for multiprofessional approaches to better patient response to antineoplastic treatment.
Keywords: Antineoplastic agents